Potensi Bakteri Tanah Penghasil Senyawa Antimikrob Untuk Menghambat Pertumbuhan Bakteri Escherichia Coli dan Staphylococcus Aureus - Mazidah Noer Inayah; Suci Indah Budiarti (Jurnal Nurse, 2021)
Antimicrobials are molecules that inhibit the growth of microbes. Some bacterial species, consisting of actinomycetes and fungi, are capable of producing antimicrobial substances. Streptomyces, commonly referred to as soil bacteria, are a group of actinomycetes that produce multiple antimicrobial agents. Other soil bacteria that may produce antibiotics include Pseudomonas, Bacillus, Nocardia, Kibdelosporangium, and Roseobacter. Thereby, soil is one of the potential sources that is capable of being used as a research sample for discovering and collecting antibiotic-producing bacteria, especially new types of antibiotics that weren't previously discovered. The latest research about antimicrobials (antibiotics) has been driven by the high number of cases of bacterial resistance. The study aims to investigate the potential of antimicrobial-producing bacteria from the soil to inhibit the pathogenic bacteria Staphylococcus aureus and Escherichia coli. The research procedure involves soil sampling, isolating the antimicrob-producing bacteria, describing the morphology of the bacterial colony and bacterial cells, purifying and regenerating the bacterial culture, and testing the activity of antimicrobial substances against E. coli and S. aureus. The study revealed four bacterial isolates: E1, E2, S1, and S2, that could possibly suppress the growth of S. aureus and E. coli. However, the antimicrobial activity of the four bacteria remained considerably smaller compared with 100 mg of chloramphenicol.